A Brief Future of Time in the Monopoly of Scientific Knowledge. Issue 4 (December 2016) - Asongu, Simplice; Nwachukwu, Jacinta
Abstract This paper provides global empirical evidence on cross-country differences in scientific and technical publications. Its purpose is to model the future of scientific knowledge monopoly in order to understand whether the impressive growth experienced by latecomers in the industry has been accompanied by a similar catch-up in scientific capabilities and knowledge contribution. The empirical evidence for the period 1994–2010 is based on 41 panels which together consist of 99 countries. The large dataset allows us to disaggregate countries into fundamental characteristics based on income levels (high-income, lower-middle-income, upper-middle-income and low-income), legal origins (English common-law, French civil-law, German civil-law and Scandinavian civil-law) and regional proximity (South Asia, Europe and Central Asia; East Asia and the Pacific; Middle East and North Africa; Latin America and the Caribbean and Sub-Saharan Africa). Three main issues are investigated: the presence or not of catch-up processes, the speed of the catch-up processes and the time needed for a complete elimination of country differences in scientific and technical publications. The findings based on absolute and conditional catch-up patterns broadly show that advanced countries will continue to dominate in scientific knowledge contribution. Policy implications are discussed.